Virulence Genes of Helicobacter pylori Increase the Risk of Premalignant Gastric Lesions in a Colombian Population - Yeison Carlosama-Rosero; Claudia Acosta-Astaiza; Carlos H. Sierra-Torres; H. Bolaños-Bravo; Andrés Quiroga-Quiroga; Juan Bonilla-Chaves (Canadian Journal of Gastroenterology and Hepatology, 2022)
Background. Genetic variability of Helicobacter pylori is associated with various gastrointestinal diseases; however, little is known about interaction with sociodemographic in the development of premalignant lesions in Colombian patients. Methods. An analytical study was conducted including cases (patients with gastric atrophy, intestinal metaplasia, and gastric dysplasia) and controls (patients with nonatrophic gastritis). Sociodemographic information was obtained using a questionnaire. Histopathological diagnosis was performed according to the Sydney System. The cagA and vacA genotypes were established using polymerase chain reaction in paraffin blocks. The effect of each variable on the study outcome (premalignant lesion) is presented as odds ratio (OR) and 95% CI. A p value of <0.05 was considered as statistically significant. Results. The vacA/s1m1 genotype increases the risk of developing premalignant lesions of the stomach (OR: 3.05, 95% IC: 1.57–5.91, p=0.001). Age and educational level showed a positive interaction with the s1m1 genotype (adjusted OR: 3.68, 95% CI: 1.73–7.82, p=0.001). The cagA genotype was not correlated to the development of premalignant lesions of the stomach (OR: 1.32, 95% CI: 0.90–1.94, p=0.151). Conclusions. The vacA genotype, age, and educational level are indicators of the risk of developing premalignant lesions of the stomach in the study population. Significance Statement. Genetic variability of H. pylori and sociodemographic information could be used to predict the risk of premalignant lesions in stomach in Colombian population.